Neurodevelopmental effects of perinatal exposure to cannabis on progeny: A narrative review - Chidimma Doris Azubuike; Oliver Grundmann; Amie J. Goodin (Drug and Alcohol Dependence Reports)
Objective: The certainty of effects on neurodevelopmental outcomes resulting from perinatal cannabis exposure is yet to be established. This review synthesizes current clinical and preclinical evidence on neurodevelopment and related functional outcomes in offspring exposed to cannabis during pregnancy or early childhood. Additionally, gaps in the literature and suggestions to bridge these gaps are provided. Method: A PubMed database search identified highest level of evidence studies focusing on in utero and early childhood cannabis exposure using keywords broadly describing outcomes alongside informal, spontaneous, and reference searches to supplement search hits. Priority was given to recent clinical studies. Findings were categorized into cognitive measures (memory, attention, and executive functioning), and diagnosis of mental health disorders (including: autism spectrum disorder [ASD], Attention deficit and hyperactivity disorder [ADHD], depression, anxiety, learning delays, and school-related performance). ` Results: Findings on effects on cognition, autism, and learning are not consistent; however, compared to children who were unexposed, prenatally exposed children consistently have higher ADHD risk, and no significant association with anxiety and depression. Exposure to higher concentrations of tetrahydrocannabinol was found to be associated with more aggressive behavior in males compared to females. Conclusion: Most findings on perinatal cannabis exposure remain inconclusive. To enhance our understanding of associated neurodevelopmental effects, future research should reassess exposure over time, employ standardized cognitive measures, use reliable exposure assessments, and methods that consider cannabis concentration and composition across generations.